Proteomics in antibiotic resistance and tolerance research: Mapping the resistome and the tolerome of bacterial pathogens. Issue 8 (6th March 2022) - Sulaiman, Jordy Evan; Lam, Henry
Abstract: Antibiotic resistance, the ability of a microbial pathogen to evade the effects of antibiotics thereby allowing them to grow under elevated drug concentrations, is an alarming health problem worldwide and has attracted the attention of scientists for decades. On the other hand, the clinical importance of persistence and tolerance as alternative mechanisms for pathogens to survive prolonged lethal antibiotic doses has recently become increasingly appreciated. Persisters and high‐tolerance populations are thought to cause the relapse of infectious diseases, and provide opportunities for the pathogens to evolve resistance during the course of antibiotic therapy. Although proteomics and other omics methodology have long been employed to study resistance, its applications in studying persistence and tolerance are still limited. However, due to the growing interest in the topic and recent progress in method developments to study them, there have been some proteomic studies that yield fresh insights into the phenomenon of persistence and tolerance. Combined with the studies on resistance, these collectively guide us to novel molecular targets for the potential drugs for the control of these dangerous pathogens. In this review, we surveyed previous proteomic studies to investigate resistance, persistence, and tolerance mechanisms, and discussed emerging experimental strategies for studying these phenotypes with a combination of adaptive laboratory evolution and high‐throughput proteomics.